Francisco Zúñiga Díaz: tres facetas de un hombre de letras - Castro Carvajal, Hiram (2018)
In this article about Costa Rica writer Francisco Zúñiga Díaz (1913-1997), three sujects related to his literary work will be studied: researcher, humorist, and novelist.